Răspuns :
E(X) = x²/x(x-1) - 1/(x-1) - 1/x
a) x≠0 si x-1≠0⇒ x≠1 ⇒ x∈R\{0,1}
b)
E(X) = x²/x(x-1) - x/x(x-1) - (x-1)/x(x-1)
E(X) = (x²-x-x+1) / x(x-1)
E(X) =( x²-2x +1) / x(x-1)
E(X) = (x-1)² /x(x-1)
E(X) = (x-1) / x
c) x≠0⇒ x∈R\{0}
d)
E(1/2) = (1/2-1)/ 1/2 = (1/2-2/2) / 1/2 = -1/2 / 1/2=-1
a) x≠0 si x-1≠0⇒ x≠1 ⇒ x∈R\{0,1}
b)
E(X) = x²/x(x-1) - x/x(x-1) - (x-1)/x(x-1)
E(X) = (x²-x-x+1) / x(x-1)
E(X) =( x²-2x +1) / x(x-1)
E(X) = (x-1)² /x(x-1)
E(X) = (x-1) / x
c) x≠0⇒ x∈R\{0}
d)
E(1/2) = (1/2-1)/ 1/2 = (1/2-2/2) / 1/2 = -1/2 / 1/2=-1